Efektivitas Penerapan Job Sheet Pembelajaran Instalasi Motor Listrik di Sekolah Menengah Kejuruan - Deris Oktageri; Ahyanuardi Ahyanuardi (Jurnal Pendidikan Teknik Elektro, 2023)
This study aims to determine the effectiveness of the application of job sheets in electric motor installation subjects at SMK N 1 Sumatera Barat. This research is a pre-experimental design with intact-group comparison. The subjects of this study were class XII Electrical Power Installation Engineering, SMK N 1 Sumatera Barat in the 2023 / 2024 school year totaling 34 people. The data collection technique uses a performance assessment rubric consisting of an assessment of practice preparation, process implementation, results, occupational safety and health, attitude, and practice reports with scoring using a Likert scale. The data analysis technique used is the analysis of learners' skills completeness, the Maan Whitney test, and effect size analysis. The results showed that the application of job sheets in terms of students' skills completeness was in the effective category, then in terms of differences in students' skills learning outcomes, it was also categorized as effective, and in terms of Effect Size analysis was in the large category and also declared effective. Therefore, it can be concluded that the application of the Electric Motor Installation1 job sheet is effective for improving student learning outcomes in Electric Motor Installation learning.